Highly-sensitive optical organic vapor sensor through polymeric swelling induced variation of fluorescent intensity - Jiang, Xiangyu (2019)
Traditional optical organic vapor sensors with solvatochromic shift mechanisms have lower sensitivity due to weak intermolecular interactions. Here, we report a general strategy to prepare a higher sensitivity optical organic vapor sensor through polymeric swelling-induced variation of fluorescent intensity. We combine one-dimensional polymeric structures and aggregation-induced emission (AIE) molecules together to form a polymer/AIE microwires array as a sensor. The prepared sensors based on different commercial polymers can successfully classify and identify various organic vapors. Among them, the poly(vinyl butyral)/AIE microwires array can detect methanol vapor as low as 0.05% of its saturation vapor pressure. According to the theory of like dissolves like, we further fabricate a polymer/AIE microwires array derived from designable polyethersulfones, through regulating their side chains, to distinguish similar organic vapors of benzene and toluene. Both experimental and theoretical simulation results reveal that specific molecular interactions between the polyethersulfones and organic vapors can improve the specific recognition performance of the sensors.